The chronicles of inflammation: uncovering of distinct patterns of NET degradation products - Schoen, Janina; Muñoz-Becerra, Marco; Knopf, Jasmin; Ndukwe, Favour; Leppkes, Moritz; Roth, Dominik; Zeitler, Anne; Frings, Verena Gerlinde; Hohberger, Bettina; Zeisberg, Victoria; Muñoz, Luis E.; Schett, Georg; et al. (Frontiers in Drug Discovery, 2024)
Aims: Neutrophils and neutrophil extracellular traps (NETs) play multifaceted roles in inflammatory diseases. If the balance of NET formation and clearance is disturbed, they contribute to the development and pathogenesis of a plethora of inflammatory diseases. They promote inflammation and tissue degradation, and occlude vessels and ducts. This study focused on the presence of NET remnants generated during the clearance by nucleases and phagocytes.Methods: NET associated parameters in serum and plasma samples from various pathological conditions were investigated. We performed fluorescence-based assays to analyze the concentration of cell free DNA and the activity of neutrophil elastase. The presence of citrullinated histone H3, as well as neutrophil elastase-or myeloperoxidase-DNA complexes were examined employing enzyme-linked immunosorbent assays.We analyzed samples from a variety of inflammatory conditions: (I) the rheumatic autoimmune diseases systemic lupus erythematosus, rheumatoid arthritis, and primary Sjögren's syndrome (II) the inflammatory bowel diseases ulcerative colitis and Crohn's disease (III) hidradenitits suppurativa and (IV) the viral-induced pathologies Coronavirus disease 2019 (COVID-19), and Post COVID Syndrome (PCS). While most NET associated parameters were detected in all inflammatory conditions, certain markers displayed disease-specific patterns. We Gelöscht: degradation markers Gelöscht: NET degradation markers compared the markers in terms of the concentration, correlations with each other and to disease activity, and their impact on sample variability. Systemic lupus erythematosus and rheumatoid arthritis were associated with increased levels of cell free DNA, and citrullinated histone H3 as well as neutrophil elastase-activity, respectively. Samples from patients with COVID-19 were characterized by elevated levels of neutrophil elastase-and myeloperoxidase-DNA complexes.Different diseases are linked to characteristic patterns of NET associated parameters. These patterns offer insights into aberrant NET formation and clearance in different pathologies and may represent key targets for treatment development.